Single-cell profiling of tumor-infiltrating TCF1/TCF7+ T cells reveals a T lymphocyte subset associated with tertiary lymphoid structures/organs and a superior prognosis in oral cancer. (August 2021) - Peng, Yu; Xiao, Liping; Rong, Haixu; Ou, Zhanpeng; Cai, Tingting; Liu, Niu; Li, Bowen; Zhang, Lizao; Wu, Fan; Lan, Tianjun; Lin, Xinyu; Li, Qunxing; et al.
Highlights: A high frequency of TCF1/TCF7 + T cells was significantly correlated with a superior prognosis in OSCC patients. TCF1/TCF7 + T cells were associated with tertiary lymphatic structure/organs. Tumor-infiltrating TCF1/TCF7 + T cells had lower expression of immune checkpoint molecules than TCF1/TCF7 - T cells. Abstract: Objectives: Despite substantial advances in treatment, clinical outcomes for oral squamous cell carcinoma (OSCC) remain unsatisfactory. Tumor-infiltrating lymphocytes (TILs) are an important prognostic factor for patients and are heterogeneous. Some studies have suggested that TCF1/TCF7 + T cells and tertiary lymphatic structure/organ (TLS) play an important role in tumor immunity. However, how they affect tumor immunity and whether they are related to prognosis in OSCC have not been reported in detail. Materials and methods: We isolated OSCC cells and performed single-cell RNA sequencing (scRNA-seq). We used immunohistochemistry (IHC) to analyze the relationship between TLSs and prognosis. Multiplex immunohistochemistry (MIHC), flow cytometry (FCM) and spatial analysis were performed to verify the characteristics of TCF1/TCF7 + T cells. The prognostic significance and upstream regulatory network of the TCF1/TCF7 + T cell subpopulation were determined by multivariate analysis and Scenic software. Results: We found a strong association between TCF1/TCF7 + T cell subsets, TLSs and prognosis. The results suggested that TCF1/TCF7 + T cells express high levels of TLS-related genes and low levels of immune checkpoint molecules. Finally, we found that TCF1/TCF7 + T cells were significantly associated with favorable outcomes. We also describe the upstream drivers that these cells rely on. Conclusions: TCF1/TCF7 + T cells could be used as a new therapeutic target to regulate the immune response of OSCC and are expected to be a new prognostic marker.